2015
DOI: 10.1161/circheartfailure.115.002130
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Exercise Training in Chronic Pulmonary Hypertension

Abstract: P ulmonary hypertension is a chronic cardiopulmonary disorder characterized by progressive increasing pulmonary vascular resistance, leading to right ventricular heart failure. 1 Prevalence of pulmonary hypertension is estimated to be 10 to 15 cases per million with a mortality rate of 15% per year. 2 Over the past 2 decades, targeted pharmacological therapies have been effective in reducing disease progression and improving the survival rate among patients with pulmonary hypertension.3,4 However, most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
4
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 51 publications
(65 reference statements)
12
113
4
8
Order By: Relevance
“…In this sense, beneficial effects of exercise in chronic heart failure patients seem to be related to the improvement in skeletal muscle oxygen delivery and utilization (Hirai et al, 2015). The positive impact of exercise is not restricted to heart failure since exercise training in patients with chronic pulmonary hypertension is associated with a significant improvement in physical performance, pulmonary arterial pressure and quality of life (Pandey et al, 2015). Claudication onset time, peak walking time and physical performance are also improved by exercise in patients with peripheral artery disease (Gardner et al, 2014).…”
Section: Article In Pressmentioning
confidence: 99%
“…In this sense, beneficial effects of exercise in chronic heart failure patients seem to be related to the improvement in skeletal muscle oxygen delivery and utilization (Hirai et al, 2015). The positive impact of exercise is not restricted to heart failure since exercise training in patients with chronic pulmonary hypertension is associated with a significant improvement in physical performance, pulmonary arterial pressure and quality of life (Pandey et al, 2015). Claudication onset time, peak walking time and physical performance are also improved by exercise in patients with peripheral artery disease (Gardner et al, 2014).…”
Section: Article In Pressmentioning
confidence: 99%
“…However, our study showed no adverse effect associated with the protocol but on the contrary its effectiveness in exercise capacity [21]. Many other rehabilitation clinics and published studies on this topic have used different protocols with different modalities such as endurance or interval training and of different duration [40]. Mereles et al [41] used a program including also 7/7 day interval bicycle ergometer training.…”
Section: Discussionmentioning
confidence: 59%
“…29 Moreover, the study showed that exercise training was associated with a significant improvement in resting PAP and peak exercise heart rate from baseline to follow-up (Figure 1). Importantly, exercise training was well tolerated and had a low dropout rate, and no major adverse events related to exercise training were reported.…”
Section: Risk Management For Ph During Pulmonary Rehabilitationmentioning
confidence: 93%
“…28, 29 Pandey et al 29 summarized the exercise and non-exercise-related adverse events reported in 17 studies. In their study, adverse effects were observed in 4.7% of all patients (N=480), two-third of which were related to exercise training (in 3.1% patients).…”
Section: Risk Management For Ph During Pulmonary Rehabilitationmentioning
confidence: 99%